Solid state physics essential concepts - Snoke, David W. (New Delhi Pearson Education, 2009)
This book centers on the unifying, essential theoretical concepts and tools of modern condensed matter physics that every student should know to read the literature. It is envisioned as a graduate text for a 1-semester course although the student is not assumed to have prior knowledge of solid-state physics because results are derived from first principles.
Keywords: Solid state physics